THE CARTESIAN CUT-CELL METHOD IN TWO DIMENSIONAL FLOOD SIMULATION - Herman, Rudi (MEKTEK, 2007)
Two dimensional dynamic models have been increasingly used for river flood simulation. This commonly uses satellite remote sensor data, recorded on a rectangular (Raster) grid. There are many important features on a flood plain, such as hedges or buildings, which do not follow the grid lines. Irregular meshes can be used to follow these features, but converting raster data to this format involves a loss of detail. The Cartesian cut-cell (CC) method uses a rectangular mesh. The edges of irregular solid bodies are located precisely with sequences of vertex coordinates. Cut-cells, which lie on the edge, are given special treatment. This allows straightforward integration of grid and vector data, potentially within a GIS based framework. This paper introduces the semi permeable internal (SPIn) boundary cut-cell method. This allows the integration of permeable boundaries, such as hedges, into the model. To explore the impact of these features, a small scale river flood event, over a field featuring a hedgerow, is simulated